Letter: faecal microbiota transplantation for irritable bowel syndrome. Authors' reply. Issue 3 (13th July 2020) - Lahtinen, Perttu; Jalanka, Jonna; Hartikainen, Anna; Mattila, Eero; Hillilä, Markku; Punkkinen, Jari; Koskenpato, Jari; Anttila, Veli‐Jukka; Tillonen, Jyrki; Satokari, Reetta; Arkkila, Perttu
Abstract : LINKED CONTENT This article is linked to Lahtinen et al and Segal papers. To view these articles, visit https://doi.org/10.1111/apt.15810 and https://doi.org/10.1111/apt.15824 .